A review on airborne microorganisms in particulate matters: Composition, characteristics and influence factors. (April 2018) - Zhai, Yunbo; Li, Xue; Wang, Tengfei; Wang, Bei; Li, Caiting; Zeng, Guangming
Abstract: Airborne microorganisms (AM), vital components of particulate matters (PM), are widespread in the atmosphere. Since some AM have pathogenicity, they can lead to a wide range of diseases in human and other organisms, meanwhile, some AM act as cloud condensation nuclei and ice nuclei which let them can affect the climate. The inherent characteristics of AM play critical roles in many aspects which, in turn, can decide microbial traits. The uncertain factors bring various influences on AM, which make it difficult to elaborate effect trends as whole. Because of the potential roles of AM in environment and potent effects of factors on AM, detailed knowledge of them is of primary significance. This review highlights the issues of composition and characteristics of AM with size-distribution, species diversity, variation and so on, and summarizes the main factors which affect airborne microbial features. This general information is a knowledge base for further thorough researches of AM and relevant aspects. Besides, current knowledge gaps and new perspectives are offered to roundly understand the impacts and application of AM in nature and human health. Highlights: Airborne microorganisms have different composition in diverse environment. These microorganisms own many important characteristics which can influence human and nature. There are many factors affecting airborne microbial features with different effects.